Medical expulsive therapy in adults with ureteric colic: a multicentre, randomised, placebo-controlled trial. Issue 9991 (25th July 2015) - Pickard, Robert; Starr, Kathryn; MacLennan, Graeme; Lam, Thomas; Thomas, Ruth; Burr, Jennifer; McPherson, Gladys; McDonald, Alison; Anson, Kenneth; N'Dow, James; Burgess, Neil; Clark, Terry; et al.
Summary: Background: Meta-analyses of previous randomised controlled trials concluded that the smooth muscle relaxant drugs tamsulosin and nifedipine assisted stone passage for people managed expectantly for ureteric colic, but emphasised the need for high-quality trials with wide inclusion criteria. We aimed to fulfil this need by testing effectiveness of these drugs in a standard clinical care setting. Methods: For this multicentre, randomised, placebo-controlled trial, we recruited adults (aged 18–65 years) undergoing expectant management for a single ureteric stone identified by CT at 24 UK hospitals. Participants were randomly assigned by a remote randomisation system to tamsulosin 400 μg, nifedipine 30 mg, or placebo taken daily for up to 4 weeks, using an algorithm with centre, stone size (≤5 mm or >5 mm), and stone location (upper, mid, or lower ureter) as minimisation covariates. Participants, clinicians, and trial personnel were masked to treatment assignment. The primary outcome was the proportion of participants who did not need further intervention for stone clearance within 4 weeks of randomisation, analysed in a modified intention-to-treat population defined as all eligible patients for whom we had primary outcome data. This trial is registered with the European Clinical Trials Database, EudraCT number 2010-019469-26, and as an International Standard Randomised Controlled Trial, number 69423238. Findings: Between Jan 11, 2011, and Dec 20, 2013, we randomly assigned 1167 participants, 1136 (97%) of whom were included in the primary analysis (17 were excluded because of ineligibility and 14 participants were lost to follow-up). 303 (80%) of 379 participants in the placebo group did not need further intervention by 4 weeks, compared with 307 (81%) of 378 in the tamsulosin group (adjusted risk difference 1·3% [95% CI −5·7 to 8·3]; p=0·73) and 304 (80%) of 379 in the nifedipine group (0·5% [–5·6 to 6·5]; p=0·88). No difference was noted between active treatment and placebo (p=0·78), or between tamsulosin and nifedipine (p=0·77). Serious adverse events were reported in three participants in the nifedipine group (one had right loin pain, diarrhoea, and vomiting; one had malaise, headache, and chest pain; and one had severe chest pain, difficulty breathing, and left arm pain) and in one participant in the placebo group (headache, dizziness, lightheadedness, and chronic abdominal pain). Interpretation: Tamsulosin 400 μg and nifedipine 30 mg are not effective at decreasing the need for further treatment to achieve stone clearance in 4 weeks for patients with expectantly managed ureteric colic. Funding: UK National Institute for Health Research Health Technology Assessment Programme.